1996
DOI: 10.1002/(sici)1097-4695(199602)29:2<151::aid-neu3>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Cellular migration and axonal outgrowth from adult mammalian peripheral nerves in vitro

Abstract: It is known that following peripheral nerve transections, sheath cells proliferate and migrate to form a bridge between nerve stumps, which may facilitate axonal regeneration. In the present investigations, cellular migration and axonal outgrowth from nerves of adult mice were studied in vitro using collagen gels. During the first 3 days in culture, profuse migration of fibroblasts and macrophages occurred from the ends of sciatic nerve segments, which had been lesioned in situ a few days prior to explantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In preliminary experiments, we observed that neurites regenerating from the peripheral nerve stump were mostly longer than those growing from the dorsal root (see also Tonge et al, 1996). Thus, the following comparative analysis between wild-type and MAP1B-deficient DRG explants is based on fibers growing from the peripheral nerve.…”
Section: Resultsmentioning
confidence: 93%
“…In preliminary experiments, we observed that neurites regenerating from the peripheral nerve stump were mostly longer than those growing from the dorsal root (see also Tonge et al, 1996). Thus, the following comparative analysis between wild-type and MAP1B-deficient DRG explants is based on fibers growing from the peripheral nerve.…”
Section: Resultsmentioning
confidence: 93%
“…Because degenerating nerves of rats, mice, chickens, and frogs are known to release factors that stimulate neurite outgrowth from sympathetic ganglia and DRGs (Richardson and Ebendal, 1982;Windebank and Poduslo, 1986;Ferguson et al, 1989;Kuffler and Megwinoff, 1994;Tonge et al, 1996), we tested effects of media conditioned by segments of lesioned and normal nerves on explanted PN-DRG preparations to see whether stimulation of axonal outgrowth of IB4-labeled axons in collagen gels would occur. However, although we observed profuse outgrowth of PGP 9.5-positive axons in the collagen gels in media conditioned by peripheral nerve segments (which was primarily abolished by a neutralizing antibody to NGF), there was no stimulation of outgrowth of IB4-labeled axons.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the axially aligned myofibroblasts is not fully understood. Axially aligned myofibroblasts may facilitate nerve regeneration by shortening the nerve gap 32 . These cells may be responsible for aligning newly synthesized collagen fibers and possibly regenerated axons during the healing process 31 .…”
Section: Morphometric Analysismentioning
confidence: 99%